Low peak oxygen uptake in relation to total heart volume as an early marker of subclinical diastolic dysfunction. - Steding Ehrenborg, Katarina; Nelsson, Anders; Engblom, Henrik; Arvidsson, Per M; Magnusson, Martin ; 0000-0003-1710-5936; Smith, J Gustav ; 0000-0001-6285-9935; Arheden, Håkan (European Heart Journal Imaging Methods & Practice, 2025)
Aim Peak oxygen uptake (VO2peak) is closely related to total heart volume (THV) in healthy individuals. This study aimed to investigate 1) the association between VO2peak and THV in subjects with subclinical diastolic dysfunction, athletes, healthy controls, and patients with established heart failure with and without preserved ejection fraction (HFpEF, HFrEF), and 2) whether VO2peak/THV-index can distinguish between subjects with subclinical diastolic dysfunction, HFpEF, HFrEF, and healthy controls. Methods Seventy participants were included: 15 with subclinical diastolic dysfunction (defined as showing only 1-2 echocardiographic signs of diastolic dysfunction, not meeting clinical diagnostic criteria), 10 athletes, 15 healthy controls and 30 heart failure patients (15 HFpEF, 15 HFrEF). VO2peak was assessed by cardiopulmonary exercise testing and THV by cardiovascular magnetic resonance imaging. Results In subclinical diastolic dysfunction, THV was a weak determinant of VO2peak (R2=0.41, p=0.01), and even weaker in heart failure (R2=0.16, p=0.03). However, THV strongly predicted VO2peak in athletes and controls combined (R2=0.87, p<0.0001). VO2peak/THV did not distinguish healthy controls from subclinical diastolic dysfunction but could reliably discriminate between healthy controls and patients with heart failure. Conclusion Subjects with subclinical diastolic dysfunction may have an altered relationship between VO2peak and total heart volume, approaching that of patients with established heart failure. Thus, this proof-of-concept study indicates that subclinical diastolic dysfunction constitutes a group of patients that may be of interest to follow over time to prevent continued deterioration of cardiac function. Furthermore, the VO2peak/THV ratio can be used to distinguish between healthy controls and overt heart failure.